Nocturnal Enuresis - Rafita Ramayati (Paediatrica Indonesiana, 1983)
In Indonesia and in other parts of the world a child with nocturnal enuresis is not an uncommon disease. Studies on nocturnal enuresis is still restricted in Indonesia. It is highly recommended to understand the disease because wetting problems can continue to more serious psychic developmental problems in our young generation. This paper represents a review on some aspects of nocturnal enuresis.